Center-Periphery Herethics in American NRMs’ Texts: Representation of Mission in Seventh-day Adventist Hymnody in Burundi - Ntamwana, Simon Ntamwana; Adzhani, Shabrina An (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
The article studied mother church-daughter church selfness and otherness with respect to American identity and new religious movements (NRMs). It examined the coexistence of the American self and Burundi internal other in the construal of mission in Seventh-day Adventist (SDA) global movement. The research material object was The Seventh-day Adventist Hymnal. Center-periphery shifts were explored in one English hymn and its Kirundi translation. Against the backdrop of social constructionism, a descriptive qualitative method based on Kristeva’s theory of signifying process and notion of herethics was used. The theory was supplemented by the notions of social semiotic by Halliday and ethical filter by House. The primary data sources included the hymns “Here Am I, Send Me” and “Nimwumv’ijwi rya Yesu”. Secondary data sources included books and articles pertaining to the topic at hand. The research advances transnational American studies by applying social constructionism to explore the translation of American religious texts outside the United States. It was found that a peripheral other anchored on Burundi SDA tradition was intercalated in the construction of American self-missional identity. The alterity decontextualized the missionary reality and social relations from hegemonic and nationalistic beliefs. Additionally, the translational marginal representation destabilized the taints of mythic innocence and manifest destiny and minimized elements suggesting transcendentalism and capitalism.